Advances in analytical methods to study cholesterol metabolism: the determination of serum noncholesterol sterols. (20th November 2012) - Andrade, Isabel; Santos, Lèlita; Ramos, Fernando
ABSTRACT: Cholesterol biosynthesis precursors and plant sterols are noncholesterol sterols currently used as relative surrogate markers of cholesterol synthesis and absorption, respectively. Its determination in serum samples is a way of diagnosing inherited disorders and also a tool for health evaluation during lipid‐lowering lifestyle/drug therapy monitoring. This approach is the only one that can be used for large‐scale clinical trials or population based studies, but, nevertheless, there is no reference method for the quantification of noncholesterol sterols in human serum samples and only analysis by GC‐FID and GC‐MS has been reported to be completely validated. Although there has been a wider use of noncholesterol sterols for the measurement and characterization of cholesterol metabolism, there is a lack of harmonization of measurements and of standardization of the methodology, which is essential for routine measurements of diagnostic utility. New recent advances in analytical methods for the determination of serum noncholesterol sterols are highlighted, focusing on the sample preparation, separation and detection techniques, which will enhance the range of applications in clinical practice. Copyright © 2012 John Wiley & Sons, Ltd.